Mój dziennik soborowy - CONGAR, Yves; MRÓWKA, Kazimierz (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
The text includes a selection of excerpts from the diary written by Yves Congar, OP, (Mon journal du Concile, Éditions du Cerf, Paris 2002), during the Second Vatican Council. The excerpts focus on Congar’s participation in the works on the key documents of the Vaticanum II and his cooperation with other prominent theologians of the time.